Public perception on Solid Waste and Public Cleansing Management Bill 2007 towards sustainable waste management in Malaysia - Fauziah, Shahul Hamid; Khairunnisa, A.K.; Siti Zubaidah, B.; Agamuthu, Pariatamby (2009)
Lack of appropriate policy is the main constraint to sustainable waste management in Malaysia. As a result, the Solid Waste and Public Cleansing Management Bill (SWPCM) was approved in 2007. Its aims are to provide an act and regulate the manag ement of solid waste and public cleansing in order to maintain proper sanitation in the country. The Bill provides for the administrative bodies authorized in MSW management and the tribunal for solid waste management services. The objective of this paper is to investigate the perception of the public in regards to the current waste management system in the country and future waste management, particularly in relation to SWPCM Bill 2007. To accomplish this, questionnaires consisting of 45 questions were randomly distributed to 694 respondents to obtain 96% confidence level. Data collected were analyzed using SPSS. Results indicated that 86% of the public is satisfied with the current waste management system. The high satisfactory level probably is related to the fact that only reliable waste management contractors are appointed and renewed after an interim period. Contracts of waste managers with high number of complaints will not be renewed and they are directed to stop their collection services. Since the passing of the Bill, government had declared that unsatisfactory contractors will be terminated from their contract once the SWPCM Bill 2007 is enforced. However, 13% is dissatisfied with the collection frequency. The public (67-78%) has relatively high knowledge on the waste management issues such as final disposal option of the municipal solid waste and others. However, the majority of the public (69%) are not aware of the existence of SWPCM Bill 2007 and its passing by the parliament in August 2007. This is mainly due to the absence of notification to the general public from the ministry level. Responses from public regarding the deposit refund system was mainly negative where majority (87%) disagreed to pay deposit for returnable packaging materials as allocated in Part X of the Bill. This is due to the fact that the system is currently absent in the country and its introduction will affect the consumers’ economy as they will lose the deposits if they did not return the materials to the manufacturer. The majority (64%) of the respondents agreed with the regulation of segregation at source. This probably is due to the high awareness on waste disposal issues. Various campaigns were aired in mass-media indicating the deteriorating quality of the environment due to the indiscriminate disposal of MSW into landfill. Nevertheless, 97% are confident that the Bill will improve the current waste management system and able to promote a more sustainable solid waste management system for the country.